Use of Foscarnet Therapy for EBV Infection following Control of PTLD with Enhancement of Cellular Immunity in a Lung-Transplant Recipient. (14th February 2011) - Afshar, Kamyar; Rao, A. Purush; Patel, Vipul; Forrester, Kevin; Ganesh, Sivagini
Abstract : Posttransplant lymphoproliferative disorder (PTLD) is a serious complication following solid organ transplantation with an annual incidence rate of 3–5% in lung-transplant recipients. Pathogenesis indicates a strong association with functional over-immunosuppression and EBV infection. Clinical improvement is generally observed with reduction in immunosuppression intensity alone. We present a case of a 24-year-old woman with EBV-associated PTLD following lung transplant where decreasing the immunosuppression improved PTLD but was ineffective against controlling the EBV infection. Foscarnet in combination with immunoglobulins was successfully administered to cause a remission of the EBV infection. This is the second case reported of a persistent EBV infection after reducing immunosuppression levels and evidence of PTLD remission that required foscarnet for EBV infection control.